2017
DOI: 10.3389/fncel.2017.00403
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Withdrawal Interneurons to Serotonin Applications in Naïve and Learned Snails Are Different

Abstract: Long-term changes in membrane potential after associative training were described previously in identified premotor interneurons for withdrawal of the terrestrial snail Helix. Serotonin was shown to be a major transmitter involved in triggering the long-term changes in mollusks. In the present study we compared the changes in electrophysiological characteristics of identifiable premotor interneurons for withdrawal in response to bath applications of serotonin (5-HT) or serotonin precursor 5-hydroxytryptophan (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 93 publications
(139 reference statements)
0
4
0
Order By: Relevance
“…It is established that serotonin (5-HT) is a basic neurotransmitter for defensive behavior in mollusks and learning on the basis of defensive reflexes (Balaban et al, 1987 ; Glanzman et al, 1989 ; Gainutdinov et al, 1999 ; Il-Han et al, 2010 ; Bogodvid et al, 2017 ). In behavioral experiments it was shown that the disruption of serotoninergic system by the neurotoxin 5.7-DHT did not change the original memory, however, led to a memory impairment after repeated reactivation (Balaban et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is established that serotonin (5-HT) is a basic neurotransmitter for defensive behavior in mollusks and learning on the basis of defensive reflexes (Balaban et al, 1987 ; Glanzman et al, 1989 ; Gainutdinov et al, 1999 ; Il-Han et al, 2010 ; Bogodvid et al, 2017 ). In behavioral experiments it was shown that the disruption of serotoninergic system by the neurotoxin 5.7-DHT did not change the original memory, however, led to a memory impairment after repeated reactivation (Balaban et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is a close relationship between noradrenergic serotonergic systems so that increase in serotonin levels causes an inhibition in receiving noradrenergic signals. The dopaminergic system plays an important role in motional activities and the functioning of dopamine is adjusted by serotonin (Bogodvid et al,2017). In addition, some of the researchers suggest the mediatory role of "Personality traits" which is a factor involved in the relationship between ADHD and Eating disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Reconsolidation of a contextual memory has been shown in invertebrate animals [49,[56][57][58][59][60][61]. The investigation of the memory formation process and memory reconsolidation in mollusks is also attractive due to the possibility of investigate the correlations between memory mechanisms and changes occurs at the cellular and receptor level [40,[62][63][64][65][66][67][68][69][70][71][72][73][74][75].…”
Section: Introductionmentioning
confidence: 99%